2013
DOI: 10.1371/journal.pone.0071807
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Elastographic Atlas of Brain Anatomy

Abstract: Cerebral viscoelastic constants can be measured in a noninvasive, image-based way by magnetic resonance elastography (MRE) for the detection of neurological disorders. However, MRE brain maps of viscoelastic constants are still limited by low spatial resolution. Here we introduce three-dimensional multifrequency MRE of the brain combined with a novel reconstruction algorithm based on a model-free multifrequency inversion for calculating spatially resolved viscoelastic parameter maps of the human brain correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
126
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 38 publications
9
126
5
Order By: Relevance
“…Reports on the mechanical properties (stiffness) of brain tissue are primarily limited to elastography [38, 39], a technique not commonly performed on in vitro model systems. Obtaining human brain tissue for ex vivo mechanical testing is challenging, therefore indentation studies are limited to animal models, and report Young’s moduli ranging from 1–2 kPa in Young’s modulus [40].…”
Section: Tissue-specific Drivers Of Metastasismentioning
confidence: 99%
“…Reports on the mechanical properties (stiffness) of brain tissue are primarily limited to elastography [38, 39], a technique not commonly performed on in vitro model systems. Obtaining human brain tissue for ex vivo mechanical testing is challenging, therefore indentation studies are limited to animal models, and report Young’s moduli ranging from 1–2 kPa in Young’s modulus [40].…”
Section: Tissue-specific Drivers Of Metastasismentioning
confidence: 99%
“…Using this technique, highly resolved maps of the magnitude (|G * |) and the phase angle (φ) of the complex shear modulus were obtained in the liver and spleen [11,14], the kidney [14] and the brain [15]. |G * | combines both elasticity and viscosity and therefore relates to the haptic material properties; φ quantifies the degree of fluidity, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[18, 28, 32, 56] In our study, the damping ratio inclusion phantom allowed us to evaluate spatial resolution in the estimated damping ratio images. This phantom indicated that the limit in damping ratio spatial resolution was 8mm using NLI.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Recent work in brain MRE has moved toward measuring small, low contrast structures to improve sensitivity to local changes in the mechanical microstucture as a vehicle to detect specific diseases. [2628]…”
Section: Introductionmentioning
confidence: 99%